2021
DOI: 10.1186/s12882-021-02451-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk predictors of acute kidney injury among HIV-positive patients presenting with sepsis in a low resource setting

Abstract: Background Acute kidney injury (AKI) is a frequently encountered clinical condition in critically ill patients and is associated with increased morbidity and mortality. In our resource-limited setting (RLS), the most common cause of AKI is sepsis and volume depletion. Sepsis alone, accounts for up to 62 % of the AKI cases in HIV-positive patients. Objective The major goal of this study was to determine the incidence and risk predictors of AKI among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It has been reported that approximately 6.0–48.5% of HIV-infected patients had a renal disease in Africa and 6.24–83% of these cases were HIVAN [ 2 ]. AKI secondary to sepsis was another major complication in sick HIV-infected patients with acquired immunodeficiency syndrome (AIDS) [ 13 ]. Numerous forms of the IC-mediated glomerular disease have been reported in HIV-positive individuals [ 14 ], referred to as HIV-associated IC kidney disease (HIVICK) with a specific description of the pattern of IC disease in the setting of HIV.…”
Section: Epidemiology and Clinical Presentationsmentioning
confidence: 99%
“…It has been reported that approximately 6.0–48.5% of HIV-infected patients had a renal disease in Africa and 6.24–83% of these cases were HIVAN [ 2 ]. AKI secondary to sepsis was another major complication in sick HIV-infected patients with acquired immunodeficiency syndrome (AIDS) [ 13 ]. Numerous forms of the IC-mediated glomerular disease have been reported in HIV-positive individuals [ 14 ], referred to as HIV-associated IC kidney disease (HIVICK) with a specific description of the pattern of IC disease in the setting of HIV.…”
Section: Epidemiology and Clinical Presentationsmentioning
confidence: 99%
“…At this time, renal function may have been seriously damaged. There is a lag in the diagnosis of AKI by Scr [17,18]. It is urgent to screen sensitive and reliable biomarkers for early diagnosis of AKI and its early treatment, so as to improve the prognosis and survival rate of patients with sepsis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, twenty-four articles were retrieved and included in the review, with a total of 9713 populations. Of the twenty-four studies, five were from Ethiopia [19][20][21][22][23], four from Tanzania [24][25][26][27], four from Nigeria [28][29][30][31], two from Uganda [32,33], one from Kenya [34], one from Cameroon [35], one from South Africa [36], one from Malawi [37], one from Senegal [38], one from Zambia [39], one from Rwanda [40], one from Burkina Faso [41], and one from DR Congo [42]. The pooled prevalence was calculated from the aforementioned studies, whereas for predictors of AKI, three studies for hemoglobin level [19,35,41], six studies for CD4 count [19,20,[24][25][26]31], and three studies for WHO clinical HIV staging [20,26,35] were used.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%